Mediatisation of Politics as An Emanating Research Paradigm: Assessment and Reflection on the Weaknesses and Potential Contributions of Strömbäck” (2008) Theory of Mediatisation of Politics - Ahmad, Nyarwi (JURNAL KOMUNIKASI INDONESIA, 2017)
Within the last couple of decades, “mediatisation” has been taking shape as a prominent research approach, which has been robustly adopted to capture and explore transformations of the roles, positions and powers of the media and their consequences on society, culture and politics. However, whilst diverse theories and concepts of mediatisation and mediatisation of politics have been advanced within the specific context of the Western-established democracy, controversial debates regarding formulations of such theories and concepts and their applications within and across democratic countries have been unresolved properly yet. Since this issue remained prevail, we lacked sufficient knowledge regarding the development of mediatisation of politics as a research paradigm and its potential theoretical contributions for understanding political communication phenomena that took shape within and across democratic countries countries. This work purposely selected the Strömbäck” (2008) theory of mediatisation of politics as a starting point to evaluate such issues. The strengths and weaknesses of this theory are discussed. Further recommendations to improve the robustness of this theory are displayed as well. Dalam beberapa dekade terakhir, “mediatisasi” sedang menjadi sebuah pendekatan penelitian yang menonjol dan diadopsi secara masif untuk menjelaskan dan mengeksplorasi transformasi peran, posisi dan kekuatan media dan konsekuensinya terhadap masyarakat, budaya dan politik. Namun, ketika beragam teori dan konsep mediatisasi dan mediatisasi politik telah berkembang dalam konteks spesifik demokrasi yang mapan di Barat, perdebatan kontroversial mengenai rumusan teori dan konsep semacam itu dan aplikasinya di dalam dan di seluruh negara demokratis belum terselesaikan dengan baik. Karena persoalan tersebut masih belum teratasi dengan baik, maka kita tidak memiliki pengetahuan yang memadai mengenai pengembangan mediatisasi politik sebagai paradigma penelitian dan kontribusi teoritis potensialnya untuk memahami fenomena komunikasi politik yang terjadi berbagai negara-negara demokrasi. Tulisan ini sengaja memilih teori Strömbäck’ (2008) tentang mediatisasi politik sebagai titik awal untuk mengevaluasi isu-isu tersebut.